2010
DOI: 10.1002/cmdc.201000050
|View full text |Cite
|
Sign up to set email alerts
|

The Binding Mode of Side Chain‐ and C3‐Modified Epothilones to Tubulin

Abstract: The tubulin‐binding mode of C3‐ and C15‐modified analogues of epothilone A (Epo A) was determined by NMR spectroscopy and computational methods and compared with the existing structural models of tubulin‐bound natural Epo A. Only minor differences were observed in the conformation of the macrocycle between Epo A and the C3‐modified analogues investigated. In particular, 3‐deoxy‐ (compound 2) and 3‐deoxy‐2,3‐didehydro‐Epo A (3) were found to adopt similar conformations in the tubulin‐binding cleft as Epo A, thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…In 1996, Höfle et al [42][43] made a comprehensive report on the production, biological properties, crystal structure, physical and spectroscopic data, as well as conformations in a solution of epothilone A and B, which provided basic data for the further study of epothilones. In 2010, Altmann et al [44] investigated the interactions Waals interactions with the protein. In order to identify the molecular factors involved in the emergence of drug resistance induced by four tubulin mutations, Navarrete et al [45] investigated the structure and dynamic properties of epothilone-β-tubulin complexes with wild-type and mutated tubulin by using molecular dynamic simulations, which is helpful to conduct in-depth understanding on the epothilones' action mechanism and SAR.…”
Section: Scheme 3 the Semi-synthesis Of Taccalonolidesmentioning
confidence: 99%
“…In 1996, Höfle et al [42][43] made a comprehensive report on the production, biological properties, crystal structure, physical and spectroscopic data, as well as conformations in a solution of epothilone A and B, which provided basic data for the further study of epothilones. In 2010, Altmann et al [44] investigated the interactions Waals interactions with the protein. In order to identify the molecular factors involved in the emergence of drug resistance induced by four tubulin mutations, Navarrete et al [45] investigated the structure and dynamic properties of epothilone-β-tubulin complexes with wild-type and mutated tubulin by using molecular dynamic simulations, which is helpful to conduct in-depth understanding on the epothilones' action mechanism and SAR.…”
Section: Scheme 3 the Semi-synthesis Of Taccalonolidesmentioning
confidence: 99%
“…In a second study, they also showed that the NMR-derived tubulinbound conformation of Epo A corresponds to a low energy conformation of the free ligand in aqueous solution. 155 Recent modeling studies by Botta and co-workers, 156 which were based on a previously developed pseudoreceptor model for b-tubulin, 148,149 also support the validity of the NMRderived bioactive conformation of epothilones (and, in addition, suggest the existence of a common pharmacophore between epothilones and taxol).…”
Section: Structural Studies and Pharmacophore Modelingmentioning
confidence: 90%
“…On the other hand, we had been successful ourselves in the elaboration of ketone 2 into epothilone A analogs bearing modified thiazole, pyrimidine or pyridine moieties in place of the natural thiazole heterocycle by means of HWE chemistry (Hauenstein & Altmann, unpublished experiments; see also refs. [26,27]). Unfortunately, the attempted HWE coupling of 2 with phosphonate 4 did not yield any of the desired olefin (Scheme 1).…”
Section: Synthesis Of Deaza-epo C (5)mentioning
confidence: 99%